Investigation on microbiology of olive oil extraction process - B. Zanoni; S. Guerrini; E. Mari; M. Migliorini; C. Cherubini; S. Trapani; M. Vincenzini (Chiriotti Editori, 2015)
Several batches of approx. 200 kg olives from Frantoio and Moraiolo cultivars were processed in an oil mill at two dates of harvesting. Samples were collected in several steps of extraction process for sensory, chemical and microbial analyses. All extracted olive oil from the second olive harvesting date was affected by sensory defects and hence classified as being "non-extra virgin". A distinction between extra virgin olive oil and nonextra virgin olive oil obtained from both harvesting dates was explained by the volatile compounds content of olive oil samples and by yeast and mould counts collected at different processing steps.